Solution structure of the reduced active site of a starch-active polysaccharide monooxygenase from Neurospora crassa - Le, Chinh N.; Phan, Han; Tran-Le, Duy P.; Tran, Diem H.; Farquhar, Erik R.; Vu, Van V. (Vietnam Journal of Science, Technology and Engineering, 2018)
X-ray absorption spectroscopy (XAS) was utilized to gain insights into the structure and electronic properties of the reduced copper active site in NCU08746, a polysaccharide monooxygenase (PMO) from Neurospora crassa that activates O2 to cleave glycosidic linkages in starch. The reaction of NCU08746 likely starts with binding of O2 to the copper(I) center. However, the solution structure of the reduced active site in NCU08746 has not been properly elucidated. In this study, we prepared Cu(I)-NCU08746 in solution, which was snap-frozen to preserve the solution structure of the copper(I) active site prior to XAS analysis. Results show that the copper(I) center in Cu(I)-NCU08746 exhibits a 4-coordinate geometry, which is different from the 3-coordinate geometry observed for some other PMOs. This difference likely arises from the coordination of the active site tyrosine residue and could contribute to the difference in activity between NCU08746 and other PMOs.